Examining International Human Rights Obligations of States to Protect Nationality, Prevent and Reduce Statelessness - Motaung, Noah Rankhudu (Curtin University, 2024)
The aim of this thesis is to examine the international human rights obligations of states to protect nationality to be able to prevent and reduce statelessness. An estimated 10 million people around the world are stateless. Statelessness is a condition of being without a nationality status. Statelessness occurs due to various factors such as discrimination, conflict of laws, migration, refugee condition, human trafficking, climate change and succession of states or transfer of territory. Although Article 15 of the Universal Declaration of Human Rights 1948 guarantees the right to a nationality to a wider spectrum of persons, many people around the world are left stateless.